2017
DOI: 10.1002/adom.201700448
|View full text |Cite
|
Sign up to set email alerts
|

Giant Enhancement of Luminescence from Phosphors through Oxygen‐Vacancy‐Mediated Chemical Pressure Relaxation

Abstract: Relaxing chemical pressure in phosphors with large‐size‐mismatched dopants, aiming at attaining high‐efficiency luminescence and a higher dopant concentration, remains a challenging subject of continuous research effort. Originally seen as undesirable and detrimental to the performance of luminescent systems, this study demonstrates that the formation of a tiny amount of oxygen vacancies favors chemical pressure relaxation (CPR), resulting in topotactic transformation of poorly luminescent parent phases to hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…The calculated La1 site distortion degree is increased from 0.2832 for the LGO matrix to 0.2943 for LGO:0.007Bi 3+ ; the distortion degree is calculated as 32 , where D represents the lattice distortion, d i is the distance from Ba to the i th coordinating O atom, d av is the average Ba–O distance, and n is the coordination number. Among the various defects, oxygen vacancies are easily generated during the annealing process of Bi-activated inorganic phosphors 18,23 . Then, we calculate the electron structures of LGO:Bi 3+ with three types oxygen-vacancy defects at the La1–La3 sites; the results are exhibited in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated La1 site distortion degree is increased from 0.2832 for the LGO matrix to 0.2943 for LGO:0.007Bi 3+ ; the distortion degree is calculated as 32 , where D represents the lattice distortion, d i is the distance from Ba to the i th coordinating O atom, d av is the average Ba–O distance, and n is the coordination number. Among the various defects, oxygen vacancies are easily generated during the annealing process of Bi-activated inorganic phosphors 18,23 . Then, we calculate the electron structures of LGO:Bi 3+ with three types oxygen-vacancy defects at the La1–La3 sites; the results are exhibited in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was demonstrated that the formation of a vacant defect could contribute to the spectral adjustment. For instance, Zhang et al 23 reported a giant enhancement of Bi 3+ luminescence that was realized by generating an oxygen vacancy, which is a new strategy for exploring novel Bi 3+ -doped phosphor materials.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure S6 in the Supporting Information, three peaks at 529.9, 531.5, and 532.7 eV can be identified from the O1sc ore-level spectrum of Bi 2.14 Sr 0.75 Ta 2 O 9 ,w hich can be assigned to lattice oxygen with perfect coordination, oxygen atoms in the vicinity of an oxygen vacancy,a nd surface-adsorbed oxygen, respectively. [4,30,31] These results indicate the existence of oxygen vacancies in Bi 2.14 Sr 0.75 Ta 2 O 9. Although thermogravimetric analysis in an oxidizing atmosphere can be used for the determination of oxygen stoichiometry in some oxygen-deficient systems, [17,18] it is difficult to apply it to oxygen-and cation-deficient Bi 2.…”
Section: Resultsmentioning
confidence: 71%
“…PALS analysis was further complemented by X‐ray photoelectron spectroscopy (XPS). As shown in Figure S6 in the Supporting Information, three peaks at 529.9, 531.5, and 532.7 eV can be identified from the O 1 s core‐level spectrum of Bi 2.14 Sr 0.75 Ta 2 O 9 , which can be assigned to lattice oxygen with perfect coordination, oxygen atoms in the vicinity of an oxygen vacancy, and surface‐adsorbed oxygen, respectively . These results indicate the existence of oxygen vacancies in Bi 2.14 Sr 0.75 Ta 2 O 9.…”
Section: Resultsmentioning
confidence: 82%
“…6−11 Employing the topochemical reaction strategy with CaH 2 as the oxygen getter, we realized that the conversion of the photoluminescence emission in Bi 3+ -doped phosphors from the visible into near-infrared (NIR) owing to the creation of randomly distributed oxygen vacancies in the reduced phases. 12,13 However, the use of CaH 2 can introduce the impure phase due to the contact-type reactions and thus call for a complex cleaning process to remove unreacted CaH 2 and byproducts. 6 In marked contrast, the noncontacted Al reduction can avoid this disadvantage where the reduction agent is remotely placed.…”
Section: Introductionmentioning
confidence: 99%